POLITIK LOKAL DALAM PERSPEKTIF STATE SOCIETY RELATION : Pemekaran Daerah, Pilkada dan â€œPergeseran Relasiâ€ Antar Elit - Hidayat, DR Syarif (Pusat Pelatihan dan Pengambangan dan Kajian Desentralisasi dan Otonomi Daerah Lembaga Administrasi Negara, 2010)
Conceptual as well as policy reform on decentralization and local autonomy post Suharto administration, at particular level, had been succeeded in opening up possibility for local government and society to play greater role in local decision making process as well as in the implementation. Yet, at the same time, this reform mainstream faced reality of ?relational bias among elites? due to changing pattern of state-society interaction post New Order. Among significant characters of this change is that society is no longer being marginalized in decision making process and policy implementation. However, the role of society cannot be seen as in term of civil society, but in this case their role had been dominated by societal actors (elites). As result, decision making process and policy implementation-both in national and local level- will be dominated by societal-state actors coalition and interest bargaining. As what can be seen in the cases of local direct election (pilkada) and regional proliferation (pemekaran daerah), each part (either state actors or societal actors) will develop formal and informal network in order to build coalition as well as bargaining their interest. In addition, each part will attempt to maximize their political and economic resources. In the future, it should not be assumed that eliminating ?pilkada? and ?pemekaran? would be the best therapy of this drawback. Instead, it would require ability to manage ?relational bias? among elites, in the process of ?pilkada? and ?pemekaran?, as well as in administration process afterward.